2003
DOI: 10.1002/gps.940
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for the management of late‐life depression in primary care

Abstract: There are effective treatments for depression in primary care. More research is needed to address the optimum treatment of depression with medical co-morbidity and to elucidate the role of newer psychological interventions. Collaborative care between primary care and specialist services is a promising new avenue for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 61 publications
1
52
0
6
Order By: Relevance
“…9 If depression was detected, evidence-supported guidance advocated the prescription of antidepressant drugs and appropriate provision of psychological care. 6,7,10 However, this indicator was retired in 2013 as part of the 2013/14 General Medical Services contract changes. 11 Irrespective of these recent Quality and Outcomes Framework changes, the focus to date has been on identifying and treating those with more severe depressive syndromes as set down in classificatory systems such as the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) 12 (major depressive disorder) or the International Statistical Classification of Diseases and Related Health Problems, 10th Revision 13 (moderate/ severe depressive disorder).…”
Section: Depression In Older Adultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 If depression was detected, evidence-supported guidance advocated the prescription of antidepressant drugs and appropriate provision of psychological care. 6,7,10 However, this indicator was retired in 2013 as part of the 2013/14 General Medical Services contract changes. 11 Irrespective of these recent Quality and Outcomes Framework changes, the focus to date has been on identifying and treating those with more severe depressive syndromes as set down in classificatory systems such as the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) 12 (major depressive disorder) or the International Statistical Classification of Diseases and Related Health Problems, 10th Revision 13 (moderate/ severe depressive disorder).…”
Section: Depression In Older Adultsmentioning
confidence: 99%
“…10 A large cross-sectional study conducted in 20 countries 4 showed that even relatively minor levels of depression are associated with a significant decrement in all quality-of-life domains and with a pattern of negative attitudes towards ageing. Subthreshold depression is also a clear risk factor for progression and the development of more severe depressive syndromes.…”
Section: Subthreshold Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, an estimated 15% of adults aged over 65 years experience symptoms of depression; a prevalence rate that is relatively consistent across countries and cultures (Beekman, Copeland, & Prince, 1999;Braam, Copeland, Delespaul et al, 2014). In older adults depression is associated with greater medical illness, disability, functional decline, and is the leading cause of suicide in this age group (Baldwin, Anderson, Black et al, 2003).…”
Section: Introductionmentioning
confidence: 99%